Futures of performance : the responsibilities of performing arts in higher education - Schupp, Karen (Routledge, 2024)
"Futures of Performance inspires both current and future artists/academics to reflect on their roles and responsibilities in igniting future-forward thinking and practices for the performing arts in higher education. The book presents a breadth of new perspectives from the disciplines of music, dance, theatre, and mediated performance and from a range of institutional contexts. Chapters from teachers across the various contexts of the US higher education system are organized according to the three main areas of responsibilities of performing arts education: to academia, to society, and to the field as a whole. With the intention of illuminating the intricacy of how performing arts are situated and function in higher education, the book addresses key questions including: How are the performing arts valued in higher education? How are programs addressing equity? What responsibilities do performing arts programs have to stakeholders inside and outside of the academy? What are programs' ethical obligations to students and how are how are those met? Futures of Performance examines these questions and offers models that can give us some of the potential answers. This is a crucial and timely resource for anyone in a decision-making position within the university performing arts sector, from administrators, to educators, to those in leadership positions"--